Maintenance of Intestinal Homeostasis in Diarrhea-Predominant Irritable Bowel Syndrome by Electroacupuncture Through Submucosal Enteric Glial Cell-Derived S-Nitrosoglutathione - Hou, Yujun; Zhao, Ying; Jiang, Huiling; Wang, Kai; Zhang, Wei; Zhou, Siyuan; Li, Ying; Zheng, Qianhua (Frontiers in Physiology, 2022)
Objective: To determine whether electroacupuncture (EA) maintains intestinal homeostasis in diarrhea-predominant irritable bowel syndrome (IBS-D) rats by repairing intestinal barrier function through enteric glial cell (EGC)-derived S-nitrosoglutathione (GSNO). Methods: Sprague–Dawley rats were randomly divided into a control group (n = 10) and an IBS-D group (n = 20). These rats received senna solution by gavage and chronic unpredictable mild stress for 14 days and were further divided into a model group (n = 10) and an EA group (n = 10). Rats in the EA group were electroacupunctured at ST25 (Tianshu), ST36 (Zusanli), and LR3 (Taichong) for 20 min every day for 14 days. The abdominal withdrawal reflex (AWR), the percentage of time spent in open arms (OT%) in the elevated plus maze test, and the diarrhea index (DI) were measured. Histopathological examination was performed to evaluate the pathological features of the colon after sacrificing the rats. Transmission electron microscopy was used to observe the EGC in the muscle and submucosal layers. Enzyme-linked immunosorbent assay was performed to detect GSNO expression in the colon. Double immunofluorescence labeling was used to detect the colocalized GFAP and GSNO expressions in the muscle and submucosal layers. Plasma FITC-dextran was used to measure intestinal permeability, whereas western blot was used to detect ZO-1 and occludin expressions in the colon. Results: OT% and ZO-1 and occludin expressions were significantly lower than those of the control group, whereas AWR scores, DI, GSNO expression in the colon, colocalized GFAP and GSNO expressions in the submucosal layer, and intestinal permeability were significantly higher than those of the control group. Structural EGC abnormalities were observed in the model group. After EA treatment, OT% and ZO-1 and occludin expressions increased significantly, whereas AWR scores, DI, GSNO expression, colocalized GFAP and GSNO expressions in the submucosal layer, and intestinal permeability decreased significantly. The EGC structure was then restored to its normal state. Conclusion: EA treatment downregulates the submucosal EGC–derived GSNO expressions, repairs the intestinal barrier by upregulating the ZO-1 and occludin expression, and improves IBS-D symptoms, including visceral hypersensitivity, anxiety, and diarrhea, suggesting a potential role for EGC-derived GSNO in the regulation of intestinal homeostasis in IBS-D rats.